Cross country linkages and transmission of sovereign risk: Evidence from China’s credit default swaps - Zhang, Wenlong; Zhang, Gaiyan; Helwege, Jean (Journal of Financial Stability, 2022)
China’s climb to a trading powerhouse has changed its position in the world and therefore its relationships with other economies. As a result, its sovereign credit risk, which we measure by the pricing of its credit default swaps (CDS), now has the potential to greatly impact other sovereign CDS spreads. Employing a dynamic approach, we find that changes in China’s sovereign risk has strong contagion effects on its goods and service providers, while China is vulnerable to contagion effects from its major importers, suggesting sovereign risk spills over to other regions via the global supply chain. China’s success hurts some of the weaker countries in Europe by competing for their customers, while China faces strong competition itself from its export-focused neighbors. FDI and portfolio investment also affect the CDS relationships between China and other economies.